2015
DOI: 10.1017/s0016756814000788
|View full text |Cite
|
Sign up to set email alerts
|

Gastropods from upper Pliensbachian–Toarcian (Lower Jurassic) sediments of Causses Basin, southern France and their recovery after the early Toarcian anoxic event

Abstract: A gastropod fauna has been studied from upper Pliensbachian -upper Toarcian deposits of two sections of the Causses Basin (southern France) in order to investigate the mode of recovery after the early Toarcian anoxic event. The fauna consists of 15 species, one of which is new (Bathrotomaria kronzwilmesorum sp. nov.). Their stratigraphical distribution shows two peaks of diversity -in the Bifrons Zone (Bifrons Subzone) and in the Aalensis Zone (Mactra Subzone) -which reflect brief times during which the oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 84 publications
(185 reference statements)
1
13
0
Order By: Relevance
“…Preliminary studies on the whole material (Conti et al 1993(Conti et al , 2004Szabó et al 1993) demonstrated that the gastropods from neptunian sills of Rocca Busambra are closely related to a faunal stock named by Szabó (1988) as Alpine type. As mentioned above, this stock inhabited topographically elevated areas of the central region of western Tethys characterized by condensed pelagic deposition (Pelagic Carbonate Platforms sensu Santantonio 1993Santantonio , 1994Santantonio & Carminati 2011) and was very different in taxonomic structure and composition from the faunas of the European epicontinental seas, the intra-Tethyan shallow water carbonate platforms and the North African belt (Szabó 1988(Szabó , 1992(Szabó , 1994Conti & Monari 2001;Gatto & Monari 2010). Its history started from the Sinemurian and can be traced at least up to the Bajocian (Intratethyan faunal unit in Conti & Szabó 1988;Conti et al 1993Conti et al , 2004Conti & Monari 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary studies on the whole material (Conti et al 1993(Conti et al , 2004Szabó et al 1993) demonstrated that the gastropods from neptunian sills of Rocca Busambra are closely related to a faunal stock named by Szabó (1988) as Alpine type. As mentioned above, this stock inhabited topographically elevated areas of the central region of western Tethys characterized by condensed pelagic deposition (Pelagic Carbonate Platforms sensu Santantonio 1993Santantonio , 1994Santantonio & Carminati 2011) and was very different in taxonomic structure and composition from the faunas of the European epicontinental seas, the intra-Tethyan shallow water carbonate platforms and the North African belt (Szabó 1988(Szabó , 1992(Szabó , 1994Conti & Monari 2001;Gatto & Monari 2010). Its history started from the Sinemurian and can be traced at least up to the Bajocian (Intratethyan faunal unit in Conti & Szabó 1988;Conti et al 1993Conti et al , 2004Conti & Monari 2001).…”
Section: Discussionmentioning
confidence: 99%
“…4, figs 1-3;Conti & Monari 1986, p. 182, pl. 2, figs 1-2, 5;Gatto et al 2015a, p. 219, text-figs 2-3), type species of the genus Laevitomaria Conti & Szabó, 1987, differs from Laevitomaria babalusciae sp. nov. in having an evenly conoidal teleoconch outline.…”
Section: Dimensions See Tablementioning
confidence: 98%
See 3 more Smart Citations